Regulation and cellular functions of class II phosphoinositide 3-kinases - Falasca, Marco; Maffucci, T. (2012)
Class II isoforms of PI3K (phosphoinositide 3-kinase) are still the least investigated and characterized of all PI3Ks. In the last few years, an increased interest in these enzymes has improved our understanding of their cellular functions. However, several questions still remain unanswered on their mechanisms of activation, their specific downstream effectors and their contribution to physiological processes and pathological conditions. Emerging evidence suggests that distinct PI3Ks activate different signalling pathways, indicating that their functional roles are probably not redundant. In the present review, we discuss the recent advances in our understanding of mammalian class II PI3Ks and the evidence suggesting their involvement in human diseases. © The Authors Journal compilation © 2012 Biochemical Society.